Numerical Study of Mixed Convection of the Nanofluids in Two-Sided Lid-Driven Square Cavity with a Pair of Triangular Heating Cylinders - Zoubair Boulahia; Abderrahim Wakif; Rachid Sehaqui (Journal of Engineering)
A numerical study is carried out concerning mixed convection of the nanofluid in two-sided lid-driven square cavity with a pair of triangular heat sources. The upper and bottom moving walls are thermally insulated while the left and right walls are cooled at constant temperature. Two-dimensional Navier-Stokes and energy equations are solved using the finite volume discretization method with SIMPLE algorithm. The method used is validated against previous works. Two cases were considered depending on the direction of moving walls. Effects of various design parameters such as Richardson number (0.1≤Ri≤100), nanoparticle volume fraction (0≤φ≤0.05), and size (25 nm≤dp≤145 nm) and type (Cu,Al2O3,TiO2) of nanoparticles on the heat transfer rate are investigated. The results of this investigation illustrate that, by reducing the diameter of the nanoparticles and Ri, the heat transfer rate increases. Moreover, it is found that by changing horizontal direction of the moving walls the heat transfer rate variation is negligible.